A subdifferential characterization of Motzkin decomposable functions. (3rd July 2019) - Martínez-Legaz, J. E.; Thibault, L.
Abstract: The paper provides a new subdifferential characterization for Motzkin decomposable (convex) functions. This characterization leads to diverse stability properties for such a decomposability for operations like addition and composition.